2014
DOI: 10.1111/jvim.12287
|View full text |Cite
|
Sign up to set email alerts
|

Serologic and Urinary PCR Survey of Leptospirosis in Healthy Cats and in Cats with Kidney Disease

Abstract: BackgroundAlthough there is serologic evidence of exposure of cats to Leptospira spp., clinical disease is rarely reported in cats.ObjectiveTo compare the seropositivity and urinary polymerase chain reaction (PCR) status for Leptospira spp. between healthy (H) cats and cats with kidney disease (KD), to investigate the serovars potentially involved, and to evaluate potential risk factors.AnimalsTwo hundred and forty client‐owned cats.MethodsCats were prospectively recruited and classified based on physical exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
126
4
19

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(156 citation statements)
references
References 40 publications
7
126
4
19
Order By: Relevance
“…We agree that reports of leptospirosis in cats are still rare and the role of cats as a source of contamination, as well as the role of leptospires in causing disease in that species might have been underestimated1.…”
supporting
confidence: 58%
See 2 more Smart Citations
“…We agree that reports of leptospirosis in cats are still rare and the role of cats as a source of contamination, as well as the role of leptospires in causing disease in that species might have been underestimated1.…”
supporting
confidence: 58%
“…In the referred study, although animals were seroreactive against Pomona1, employing only serology and PCR we cannot be sure about the real infecting serovar. Therefore, the bacteriological isolation of the agent from clinical species remains mandatory for a better understanding of leptospirosis in cats and the real role of those animals on the epidemiology of the infection.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…67,70 A study by Rodriguez and colleagues has compared seropositivity and urinary PCR between CKD cats and non-age matched controls. 68 Seropositivity was significantly different between the two groups (7.2% non-CKD, 14.9% CKD cats) although PCR results were not. 68 However, a further study demonstrated no significant difference in seroprevalence between azotemic and non-azotemic cats.…”
Section: Association Of the Development Of Chronic Kidney Disease Witmentioning
confidence: 94%
“…[66][67][68][69] Experimental studies suggest that cats are largely resistant to acute leptospirosis although reports of clinical cases suggests that this is a possibility. 67,70 A study by Rodriguez and colleagues has compared seropositivity and urinary PCR between CKD cats and non-age matched controls.…”
Section: Association Of the Development Of Chronic Kidney Disease Witmentioning
confidence: 99%